Water transport and leaf water relations in winter wheat crops - Wallace, James S. (1978)
Leaf water potential (psiL) in winter wheat (Triticum aestivum L cv Huntsman) was related to crop evaporation rate and soil water potential. During the day psiL responded primarily to changes in evaporation, whereas seasonal changes in psiL resulted from changes in soil water potential. Hysteresis in the relation between psiL and the flow of water through the plants was attributed to changes in water storage in the soil-plant system. Modelling this gave estimates of the hydraulic resistance (R) and capacitance (C) of the soil-plant system which agreed with independent estimates. Components of R and C were also estimated. Then the soil water potential (psiS) was high, the largest hydraulic resistance could be atrributed to the soil-root system, the stem resistance was half of this. Resistance to water flow in the soil-root system increased when psiS was low, and there was evidence of large water potential gradients in the soil around the roots. There was a systematic decrease in leaf osmotic potential (psiPi) and increase in leaf turgor potential (psiP, ) from the bottom to the top of the stem. When psiL in the youngest leaves decreased so did psiPi, apparently by a combination of dehydration and solute accumulation in the leaves. Osmotic adaptation therefore tended to maintain psiP during water stress. Maintenance of psiP was important since stomatal conductance was reduced at low-leaf turgor potentials, irrespective of irradiance.